Covid-19 Pandemic-Related Stress and Coping Strategies Among Adults with Chronic Disease in Southwest Ethiopia - Girma A (Dove Medical Press, 2021)
Abel Girma,1 Ermias Ayalew,2 Gebremeskel Mesafint2 1Department of Reproductive Health and Human Nutrition, Mizan-Tepi University, Mizan-Aman, Ethiopia; 2Department of Nursing, Mizan-Tepi University, Mizan-Aman, EthiopiaCorrespondence: Abel GirmaMizan-Tepi University, Mizan-Aman, EthiopiaEmail abeloo405@gmail.comBackground: The outbreak of the novel coronavirus disease 2019 (COVID-19) pandemic presented a great threat to the physical and mental health of the general population. Patients with chronic disease have always been vulnerable to stressful life conditions. Therefore, determining the perceived stress and coping strategies among chronic disease patients is crucial to minimize the mental health consequences related to the outbreak.Objective: This study aimed to determine COVID-19-related stress and coping strategies among adults with chronic disease in southwest Ethiopia.Methods: An institution-based cross-sectional study was conducted among 613 randomly selected adults with chronic disease in southwest Ethiopia. A multiple linear regression analysis was used to determine the relationship between the COVID-19-related stress score and coping strategy types, and independent sample t-tests and ANOVA tests were conducted. Statistical significance was accepted at p-values < 0.05.Results: More than two-thirds of study participants (68.4%) were moderately stressed, 13.9% were severely stressed, and 17.8% had low levels of perceived stress. Active coping (β=1.238, 95% CI: 0.0 to 2.477), denial (β=3.678, 95% CI: 2.44 to 4.915), behavioral disengagement (β=3.669, 95% CI: 2.193 to 5.146), self-blame (β=1.722, 95% CI: 0.146 to 3.297), and religion (β=3.443, 95% CI: 2.028 to 4.858) coping strategies positively predicted the COVID-19-related stress score. Only the acceptance coping strategy (β=− 2.710, 95% CI: − 3.926 to − 1.493) negatively predicted the COVID-19-related stress score.Conclusion: Significant numbers of participants suffered from moderate to severe perceived stress levels due to the COVID-19 outbreak. Both adaptive and maladaptive coping strategy types were significantly associated positively and negatively with perceived stress score among adults with chronic disease. There were significant differences in the mean scores of perceived stress and categories of variables such as family size, duration of disease, and age of the participants.Keywords: COVID-19-related stress, coping strategies, chronic disease, southwest Ethiopia